Early clinical outcomes after small incision lenticule extraction surgery (SMILE). Issue 1 (February 2018) - Recchioni, Alberto; Hartwig, Andreas; Dermott, Jay; Vaswani, Sundeep; Bhatt, Jay; Morris, Robert; O'Donnell, Clare
Highlights: Ophthalmic surgery can lead to or exacerbate dry eye signs and symptoms. SMILE appears to be a safe and efficacious option for the correction of myopia and myopia with astigmatism. Early clinical outcomes data from surgeons' first procedures compare favourably to excimer based LASIK and surface ablation techniques. Small incision lenticule extraction (SMILE) may have less impact on the ocular surface compared to other forms of laser vision correction. Abstract: Purpose: Dry eye is known to impact on clinical outcomes after laser vision correction and the use of a newer 'all femtosecond laser' surgical approach may be associated with less impact on the ocular surface post-operatively. The purpose of this study was to evaluate the early clinical outcomes and tear instability after the first small incision lenticule extraction (SMILE) cases undertaken by three surgeons at a single site in the UK. Methods: Retrospective audit. Seventy-one eyes of 37 patients underwent SMILE surgery using the Zeiss VisuMax laser system (Carl Zeiss Meditec, Germany). Uncorrected and corrected distance visual acuity, spherical equivalent refraction, fluorescein enhanced tear break up time, simulated keratometry and complications were evaluated pre- and post-operatively where applicable. Results: The study population consisted of 21 males and 16 females. The mean ± standard deviation age was 33 ± 8 years. The results showed that 100% of eyes achieved 20/40 or better and 88% achieved 20/20 or better uncorrected distance visual acuity. The spherical equivalent refraction after surgery was within ±0.50D in 82% of eyes at three months. There was no significant difference in tear break up time from pre-operative levels at three months. Complications were infrequent. Conclusions: This early data from surgeons' first SMILE procedures suggest SMILE provides good outcomes in terms of refractive predictability and visual acuity with minimal impact on the tear film. Longitudinal research will further improve our understanding of the longer-term impact of SMILE on clinical outcomes, ocular surface metrics and patient reported outcomes.